Tennis specific limitations in players with an ACL deficient knee - Maquirriain, J.; Megey, P. J. (British Journal of Sports Medicine, 2006)
Background: Complete rupture of the anterior cruciate ligament (ACL) causes significant alteration of knee joint kinematics. Untreated patients often develop joint instability, chronic articular degeneration, and knee dysfunction. Demands on the ACL produced by playing tennis have not been investigated.